Estudo da resposta do campo de escoamento à variação da velocidade das correntes de contorno oeste no embaiamento de Tubarão-ES - Barreto, Fernando Túlio Camilo (2014)
The shear resulting from the interaction between the Brazil Current (BC) and North Brazil Under Current (NBUC) is one of the main factors responsible for important features found off the coast of the Espírito Santo (ES)-Brazil, as eddies and meandering. Nevertheless, there are few studies showing the influence of BC/NBUC system in mesoscale dynamics of this region, which is of crucial importance to the country due to its oil potential. In this work sensitivity experiments were performed using the Delft3D model, which were varied the speed of the CB and NBUC, in order to study the flow field response to this variation, and thus contribute in understanding the mesoscale dynamics of ES adjacent oceanic region. For this, velocity cross-sections, the intrusion of cold water, the Tubarão Eddy (TE), and the Cyclonic Tubarão Eddy (CTE), were analyzed. The results showed that the variation of the current velocity induced a change in the vertical extension of the currents and a longitudinal translation of their cores, this being responsible for the variation of the cold water intrusion on the shelf observed in the experiments. Regarding the eddies, was found a dominance in the TE dynamics by the BC, while changes in the speed of both the CB as the NBUC induced significant changes in CTE. This difference between TE and CTE are probably related to differences in the vertical extension of the two vortices. While the sign of TE was identified only in the BC, the CTE was identified in BC and NBUC. At the end of the work it was concluded that the variations of the current velocity were not able to modify the mesoscale scenario in the region, as occurred in Soutelino et al. (2013) for their sensitivity experiments.